EVALUASI SISTEM DAN DAMPAK LINGKUNGAN PENGELOLAAN AIR TERPRODUKSI PADA SUMUR X1 PT MGBI LAPANGAN WUNUT - Dhana J, Ida Bagus; Budiarsa Suyasa, I Wayan; Sara Wijana, I Made (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2024)
PT Minarak Gas Brantas Inc.'s operations in the Wunut Field involve the production of waste in various forms, primarily liquid waste, with produced water being the most significant type. Proper management of this produced water waste is crucial to prevent environmental pollution and ensure economic and environmental sustainability. The company manages this waste by reinjecting it into the reservoir to prevent groundwater contamination. To ensure the effectiveness of this reinjection process, they have created a groundwater flow pattern map (flow net) at three locations near the injection well: LP1 in Keduung Boto Village, LP2 in Candi Pari Village, and LP3 in Candi Pari Village, all in Sidoarjo Regency. This helps in understanding the potential spread of pollutants in the soil and underground water, aiding in environmental pollution monitoring and managment.The groundwater from this area is used for various human activities like bathing, cooking, and washing. However, based on water quality standards outlined in Ministry of Health Regulation No. 2 of 2023, the produced water from Well X-1 in the Wunut Field does not meet the required TDS (Total Dissolved Solids) content standards due to a decline in hydrocarbon fluid production, resulting in a separator efficiency of 74,86%. Additionally, lab tests and flow net results indicate that the TDS levels in LP1, LP2, and LP3 do not meet the sanitation and hygiene water quality standards, suggesting potential seepage in these locations that could contaminate groundwater. Keywords: Oil; Gas Produced Water; Gas Separator Eficiency; Groundwater Flow